Variasi morfologis induk udang galah (Macrobrachium rosenbergii de Man, 1879) Populasi Siratu, GIMacro, Mahakam, dan Bengawan Solo - Nurul Suwartiningsih; Listiatie Budi Utami (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2020)
Giant freshwater prawn is a native Indonesian freshwater prawn, which has the largest body size among other freshwater prawn. Efforts to increase the production of giant prawns can be done by genetic improvement of the parent. The main basis for conventional genetic improvement of giant freshwater prawns is availability of morphological variation information. This study is to determine the morphological variations of the giant prawn broodstock of Siratu, GIMacro, Mahakam, and Bengawan Solo populations which are cultured in Unit Kerja Budidaya Air Payau Balai Budidaya Udang Galah (UKBAP BBUG) Samas. Through this research it is expected to determine the broodstock with a profitable character that is able to produce hybrids with profitable characters as well. Baseline morphometrics were observed from the ratio of cephalothorax: abdomen length, ratio of carapace: rostrum length and ratio of carapace: abdomen length. Morphological variations were observed using 58 characters which included morphometric, meristic and morphological characters. The results showed the largest ratio of cephalothorax and abdomen average length owned by Bengawan Solo population, while the largest ratio of carapace and abdominal average length owned by Mahakam. The highest morphological variation is owned by Mahakam with 52% similarity. The lowest morphological variation is owned by GIMacro and Siratu populations with 80% similarity. The giant prawn broodstock which is expected to produce hybrid with profitable character is the broodstock from Bengawan Solo population.Keywords: Giant freshwater prawn, Morphological variation, SiratuGIMacro, Mahakam, Begawan Solo ABSTRAKUdang galah merupakan udang air tawar asli Indonesia, yang memiliki ukuran tubuh terbesar di antara udang air tawar lainnya. Sejauh ini beberapa upaya peningkatan produksi udang galah perlu kajian mendalam, di antaranya melalui perbaikan genetik induk. Adapun informasi penting yang harus diketahui untuk perbaikan genetik induk udang galah adalah karakterisasi morfologis induk udang galah yang diperkirakan unggul. Tujuan dari penelitian ini adalah untuk mengetahui variasi morfologis induk udang galah populasi Siratu, GIMacro, Mahakam, dan Bengawan Solo yang dibudidayakan di Unit Kerja Budidaya Air Payau Balai Budidaya Udang Galah (UKBAP BBUG) Samas. Adapun karakter morfometrik utama yang diamati meliputi rasio rerata panjang sefalotoraks: abdomen, rasio rerata panjang karapaks: panjang rostrum dan rasio rerata panjang karapaks: abdomen. Selain itu, 58 karakter variasi morfologis juga diamati, meliputi karakter morfometrik, meristik dan morfologi. Hasil penelitian menunjukkan rasio rerata panjang sefalotoraks dan abdomen terbesar dimiliki populasi Bengawan Solo, sedangkan rasio rerata panjang karapaks dan abdomen terbesar dimiliki populasi Mahakam. Variasi morfologis tertinggi dimiliki populasi Mahakam dengan similaritas 52% terhadap ketiga populasi yang lain. Variasi morfologis terendah dimiliki populasi GIMacro dan Siratu dengan similaritas 80%. Induk udang galah yang diharapkan dapat menghasilkan hibrid dengan karakter unggul adalah induk populasi Bengawan Solo.Kata kunci: Udang galah, Variasi morfologis, Siratu, GIMacro, Mahakam, Bengawan Solo